Fuel Subsidy Reform and Environmental Quality in Nigeria - Opeyemi Akinyemi (International Journal of Energy Economics and Policy, 2015)
The study examines the existence of a long run effect of fuel subsidy reform on environmental quality in Nigeria for the period of 1970-2012 using the Johansen and the Engle-Granger two step co-integration procedure techniques. The study developed a three case scenarios including i) a case of subsidy payment, ii) a case of effective subsidy and, iii) a case of no subsidy payment. Findings from the study supported evidence of a long run sustainable equilibrium model. Also, our estimation results showed that the first and the last case scenario do not significantly influence environmental quality. This implies that subsidy payment in Nigeria does not enhance access and consumption of liquid fuel. On the other hand, the interaction of sound regulatory framework with subsidy payment (the case of effective subsidy) significantly exerts a responsive influence on environmental quality.